Effects of word-evoked object size on covert numerosity estimations - Dumitru, Magda L.; Joergensen, Gitte H. (Frontiers in Psychology, 2015)
We investigated whether the size and number of animals mentioned in digit-word expressions influenced participants' performance in covert numerosity estimations (i.e., property probability ratings). Participants read descriptions of big or small animals standing in short, medium, and long rows (e.g., There are 8 elephants/ants in a row) and subsequently estimated the probability that a health statement about them was true (e.g., All elephants/ants are healthy). Statements about large animals scored lower than statements about small animals, confirming classical findings that humans perceive groups of large objects as being more numerous than groups of small objects (Binet 1890) and suggesting that object size effects in covert numerosity estimations are particularly robust. Also, statements about longer rows scored lower than statements about shorter rows (cf. Sears 1983) but no interaction between factors obtained, suggesting that quantity information is not fully retrieved in digit – word expressions or that their values are processed separately.